CeRNA Expression Profiling Identifies KIT-Related circRNA-miRNA-mRNA Networks in Gastrointestinal Stromal Tumour - Jia, Ning; Tong, Hanxing; Zhang, Yong; Katayama, Hiroshi; Wang, Yuan; Lu, Weiqi; Zhang, Sumei; Wang, Jin (Frontiers in Genetics, 2019)
Gastrointestinal stromal tumors (GISTs) are the most common human sarcomas and typically locate in the stomach or small intestine. Although circular RNAs (circRNAs) were identified to plays vital roles in tumor oncogenesis and progression, the molecular basis for aggressive tumor biology of these circRNAs in GISTs remains unclear. In this study, we applied SBC ceRNA microarrays to screen for tumor-specifc circRNA profiles in GISTs and identified that a total of 5770 circRNAs and 1815 mRNAs were differentially expressed in GISTs. Three significantly differential circRNAs (circ_0069766, circ_0084097, and circ_0079471) and their host genes (KIT, PLAT, and ETV1) were also verified in 68 pairs of GIST and adjacent normal gastric tissues by qRT-PCR. GIST-specific circRNA-miRNA-mRNA regulatory networks analysis demonstrated that the specific KIT related regulatory networks were involved in the three circRNAs, the circRNA host genes and three miRNAs (miR-142-5p, miR-144-3p and miR-485-3p), which may be key regulators of GISTs and served as molecular biomarkers and potential therapeutic targets for this malignant disease.